AB1099 Counselling on family planning and contraception, and pregnancy outcome in women with rheumatic diseases: a national survey of 398 patient-reported questionnaires from 24 rheumatology centers. (15th June 2017) - Lazzaroni, MG; Dall'Ara, F; Andreoli, L; Carini, C; Rodrigues, M; Reggia, R; Bartoloni-Bocci, E; Gerli, R; Chighizola, CB; Gerosa, M; Meroni, PL; Sinigaglia, L; et al.
Abstract : Background: Rheumatic diseases (RD) predominantly affect young women during reproductive age. Pregnancy, contraception and family planning (FP) are crucial for the quality of life of these patients. Objectives: We aimed to investigate 'women's health' through a self-reported questionnaire. Answers from patients with connective tissue diseases (CTD) vs chronic arthritis (CA) were compared. Methods: 24 centres distributed the questionnaire (65 multiple-choice and 12 open-answer questions) to women with RD (18–45years) regularly attending their outpatient clinics. Results: Answers were collected from 249 CTD vs 149 CA patients. Their desire to have children was influenced by RD in 40% of cases: half of them reduced the number of children they wanted (Table 1). 39% CA vs 29% CTD were afraid of being mother because of disability. 24% CTD vs. 18% CA had at least one miscarriage; 21% CTD vs. 2% CA had more than one. 31% CTD and 34% CA were never asked about their desire to have children. 61% CTD vs 70% CA received counselling about contraception, given by a gynaecologist (G) (58% vs 64%), rheumatologist (R) (22% vs 14%) or both (7% vs 9%). 60% in both groups received a counselling before pregnancy: 34% vs 39% from R and G, 14% vs 22% by R. This positively changed family planning in 64% vs 59%. We created a Knowledge Index (based on the average of the normalized performed scores on 6 key questions for different sections): 55% CTD patients vs 44% CA had a medium-high score. A higher score directly correlated with the desire to became pregnant and with a multidisciplinary counselling. Conclusions: This survey suggested that CTD have a major impact on FP and family size, possibly mediated by the increased rate of miscarriages as compared to CA. Concerns about reproductive issues could be positively overcome by adequate counselling. Rheumatologists should implement the discussion about FP and the compatibility of drugs with pregnancy in the management of young women with RD, especially those with CTD for whom contraception and pregnancy have particular implications. Acknowledgements: Statistical analysis supported by an unrestricted grant by UCB Pharma Thanks to Patients' Associations and Participants Disclosure of Interest: None declared